2018
DOI: 10.1024/0300-9831/a000285
|View full text |Cite
|
Sign up to set email alerts
|

No Association between Vitamin D and Acute Respiratory Tract Infections Amongst Elite New Zealand Rugby Players and Rowers

Abstract: Abstract. Upper respiratory tract infections are the most common infections reported by elite athletes. Low vitamin D status has been associated with an increased risk of upper respiratory tract infections. The aim of this study was to investigate associations between serum 25-hydroxyvitamin D (25(OH)D), salivary immunoglobulin A (S-IgA) concentrations, and acute respiratory tract infections (colds/flu) (ARI) in elite rowers and rugby players. A total of 53 (23 rugby players, 30 rowers) elite New Zealand athle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 28 publications
2
8
0
Order By: Relevance
“…In the volunteers in this study, the initial mean 25(OH)D concentration was 16.7 ng•ml -1 (range -12.5-19.7 ng•ml -1 ) and 25.7 ng•ml -1 (range -20.8-35.4 ng•ml -1 ) in the deficient and sufficient groups, respectively. It is possible that the lack of variation in 25(OH)D concentration between groups may have reduced the ability to detect a relationship between vitamin D and URTI episodes, which is consistent with the findings reported by Scullion et al [39]. It should be noted that the reduction in URTI risk achieved via vitamin D supplementation appears to be greater in cohorts with severe vitamin D deficiency [17,40,41], which may also explain the lack of association between 25(OH)D concentration and URTI in the current study.…”
Section: Discussionsupporting
confidence: 89%
“…In the volunteers in this study, the initial mean 25(OH)D concentration was 16.7 ng•ml -1 (range -12.5-19.7 ng•ml -1 ) and 25.7 ng•ml -1 (range -20.8-35.4 ng•ml -1 ) in the deficient and sufficient groups, respectively. It is possible that the lack of variation in 25(OH)D concentration between groups may have reduced the ability to detect a relationship between vitamin D and URTI episodes, which is consistent with the findings reported by Scullion et al [39]. It should be noted that the reduction in URTI risk achieved via vitamin D supplementation appears to be greater in cohorts with severe vitamin D deficiency [17,40,41], which may also explain the lack of association between 25(OH)D concentration and URTI in the current study.…”
Section: Discussionsupporting
confidence: 89%
“…We screened the full text of 33 studies and excluded nine that did not meet the selection criteria. Of the 24 studies included, 10 reported the association between 25(OH)D and the risk of ARTI [25,29,31,32,33,34,35,36,37,38], eight reported on the severity of ARTI [14,16,39,40,41,42,43,44], and six reported on both the risk and severity [13,15,26,45,46,47].…”
Section: Resultsmentioning
confidence: 99%
“…One of the studies [14] did not have vitamin D as the sole supplement; it included fish oil and protein. Table 1 presents the characteristics of eligible studies (2018) [16] 53 All female --------N/A High vitamin D concentrations seen in subjects Fikratkerimov et al…”
Section: Resultsmentioning
confidence: 99%
“…As a result of these differences, the worldwide prevalence of low vitamin D status varies according to the level of 25(OH)D utilized to define sufficiency [30,33] In the present review, six studies used ES classification [11,13,15,[17][18][19] only 2 used IOM [9,10] the other 3 made no mention in their articles. The individual's baseline vitamin D level is important since those with normal or near-normal levels receiving vitamin D supplementation are unlikely to exhibit physiological benefits [33] It has been emphasized that only those with depleted vitamin D stores should receive supplementation to ensure treatment efficiency and minimize risk of adverse events [33 In the present review, 7 studies examined the effects of supplementation on deficient subjects [9,12,13,15,[17][18][19] while 3 included non-deficient subjects [10,11,16] . One had no information [14]…”
Section: Cathelicidinmentioning
confidence: 99%